Antioxidant, analgesic and anti-inflammatory activities of Leucas cephalotes (Roxb.ex Roth) Spreng - Bhukya Baburao; Anreddy Rama Narsimha Reddy; Gangarapu Kiran; Yellu Narsimha Reddy; Gottumukkala Krishna Mohan (Universidade de São Paulo, 2010)
The whole plant of the methanolic extract from Leucas cephalotes was screened for invitro antioxidant (using the DPPH method), invivo analgesic (using hot plate test in mice) and anti-inflammatory (using rat paw edema test) activities. The methanolic extract of Leucas cephalotes (MELC) scavenged the DPPH radicals in a dose-dependent manner. The IC50 value to scavenge DPPH radicals was found to be 421.3µg/ml. A significant (p<0.0005) analgesic activity was observed at 60 min with 200 mg/kg, and 400 mg/kg exhibited maximum activity. The maximum anti-inflammatory response was produced at 3 hr and 2 hr with doses of 200 and 400 mg/kg, respectively. These results suggest that the methanolic extract from Leucas cephalotes exerts significant analgesic and anti-inflammatory effects, which were comparable with standard drugs. O extrato metanólico total de Leucas cephalotes foi submetido à triagem para as atividades antioxidante in vitro (utilizando o método DPPH), analgésica (utilizando teste da placa quente, em camundongos) e antiinflamatória (utilizando teste de edema da pata de rato), nas doses de 200 e 400 mg/kg. O extrato metanólico de Leucas cephalotes (MELC) inativou radicais difenil picril hidrazila (DPPH) de forma dose-dependente. O IC50 para essa atividade foi de 421,3 µg/mL. Observou-se atividade analgésica significativa (p<0,0005) a 60 minutos, com 200 mg/kg, e, com 400 mg/kg, observou-se atividade máxima. A resposta antiinflamatória máxima foi produzida, respectivamente, em 3 h e 2 h, com doses de 200 e 400 mg/kg. Estes resultados sugerem que o extrato metanólico de Leucas cephalotes apresenta efeitos analgésico e antiinflamatório significativos, comparáveis aos fármacos padrão.